Utilisation of spent tyre pyrolysis char as activated carbon feedstock: The role, transformation and fate of Zn. (1st May 2021) - Jones, Isabelle; Preciado-Hernandez, Jorge; Zhu, Mingming; Zhang, Juan; Zhang, Zhezi; Zhang, Dongke
Graphical abstract: Highlights: ZnO and ZnS catalyse activation of spent tyre pyrolysis char in CO2 . ZnO-loaded char has higher BET surface area than acid washed char at 950 °C. Carboreduction of ZnO by char to form Zn vapour and CO increases burn-off. ZnS dissociates above 600 °C to Zn and S, where Zn reacts with CO2 to reform ZnO. Abstract: Utilisation and minimisation of spent tyre stockpiles has been made more viable by pyrolysis and activation to produce low-cost activated carbons. The unique chemical composition of spent tyre pyrolysis chars (STPC), particularly the high Zn content, has been shown to affect their activation and subsequent utilisation. Nonetheless, little research has examined exactly how these additives affect activation and, ultimately, what becomes of Zn during the activation process. This paper presents a systematic study of the effect of Zn, ZnO and ZnS on the physical properties of STPC and their transformation mechanisms during CO2 activation. Samples of acid-washed STPC with and without ZnO and ZnS addition were activated using a fixed-bed reactor in 66.7%v/v CO2 for 3 h at 850, 950, 1000 and 1050 °C. Under these conditions, both ZnO and ZnS were found to act as a catalyst during activation, increasing surface area, pore volume and burn-off. During the activation, ZnO was reduced by C to form elemental Zn and ZnS was thermally decomposed to release Zn and S. Thermogravimetric analysis of Zn and its compounds above 600 °C, separately and mixed with acid-washed char, under CO2 confirms that ZnO and ZnS dissociate to release Zn( v ) that further reacts with CO2 or S to reform ZnO or ZnS. However, Zn is progressively removed from activated carbon at temperatures between 950 °C and 1050 °C. These results have direct implications for the utilisation of SPTC as a feedstock for activated carbon, and the production of Zn-loaded activated carbons.